2017
DOI: 10.1038/ncomms15384
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of gelatinase B/MMP-9 does not attenuate colitis in murine models of inflammatory bowel disease

Abstract: One third of patients with inflammatory bowel disease (IBD) inadequately respond to anti-TNF treatment and preclinical data suggest that matrix metalloproteinase-9 (MMP-9) is a novel therapeutic target. Here we show that IBD clinical and histopathological parameters found in wild type mice challenged with three different models of colitis, acute and chronic dextran sodium sulphate (DSS), and acute 2,4,6-trinitrobenzenesulfonic acid-induced colitis are not attenuated in MMP-9 knockout mice. We find similar colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 53 publications
2
37
1
Order By: Relevance
“…We tested the protein levels of MMP-2 in our mmp-9 -/- mice and these were not significantly altered. In addition, by RNAseq analysis we found that basal levels of all mouse MMP mRNAs, except that of MMP-9, were not altered in our WT (n = 8) versus mmp-9 -KO mice (n = 8) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested the protein levels of MMP-2 in our mmp-9 -/- mice and these were not significantly altered. In addition, by RNAseq analysis we found that basal levels of all mouse MMP mRNAs, except that of MMP-9, were not altered in our WT (n = 8) versus mmp-9 -KO mice (n = 8) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our knockout line has a severe subfertility phenotype [ 22 ]. For these reasons and in view of the increasing awareness about possible confounding influences imposed by differences in genetic backgrounds between wild-type and knockout mice [ 23 , 24 ] and by possible interference by differences in environmental conditions [ 25 ] and to avoid clinical bias on the basis of fur color, we further backcrossed our mmp-9 knockout mice (mmp-9 -/- ) till these became black [ 26 ]. We used in all forthcoming experiments black animals from the 13 th generation backcross into C57Bl/6.…”
Section: Methodsmentioning
confidence: 99%
“…9 During our colitis experiments, WT and MMP-9 -/- mice were co-housed according to phenotype. This implicates that WT and MMP-9 -/- mice received the same drinking bottle with normal drinking water or water supplemented with DSS, which excludes potential DSS intake-related differences within the same cage.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, a recent report argued against its significance because MMP-9 inhibition does not attenuate murine colitis. 33 In addition, recent clinical trials with MMP-9 antagonist have not demonstrated significant efficacy in patients with moderate-to-severe UC or CD. 34 Such results obscure the significance of MMP-9 for the regulation of inflammation.…”
Section: Groupmentioning
confidence: 99%